GENOTYPIC VARIATIONS IN REPRODUCTIVE MORPHOLOGY AND ANATOMY OF HOT CHILLI (Capsicum chinense Jacq.) GROWN UNDER ELEVATED CO2 AND TEMPERATURE (Applied Biological Research, 2023)
Two cultivars of hot chilli (Capsicum chinense Jacq.) cv. ‘Manipur’ and cv.  ‘Assam’ were used to study the impact of elevated carbon dioxide (eCO2) and elevated temperature (eTemp) on some of their reproductive  morphological features and anatomy. Hot chilli were grown under carbon  dioxide temperature gradient tunnels (CTGT) wherein different  concentration of CO2 and temperature were maintained. The study  revealed significant variations in pollen number, diameter and viability  under variable regimes of eCO2 and eTemp. Highest pollen number,  diameter and viability was found in the plant grown under CTGT II.  Significant increase in xylem and phloem number in cv. ‘Manipur’ under  CTGT II revealed better adaptability of crop due to improved solute  transport to the growing regions. Anomaly in flower development was  evidenced in CTGT III causing improper fertilization due to elongated and  curved stylethat might obstruct fertlization, although a genotypic  variation existed. Therefore, hot chilli cv. ‘Manipur’ can be grown under  eCO2 (550 ppm) and eTemp (2oC higher than ambient conditions).
Keywords: Elevated CO2; temperature; hot chilli; phloem; pollen; stigma bending; water status; xylem; viability